Ecology and biology of Halophila ovalis (R. Br.) Hook. f. - Chin, Pei Ju.
Merambong and Tg. Adang Laut shoals are located at the most southern part of Peninsular Malaysia. The seagrasses at these shoals formed canopies in the seagrass meadow which can be seen during low spring tide. Halophila ovalis which is dominant in Merambong and Tg. Adang Laut shoals, live successfully even with the existence of interspecific and intraspecific competition. It also adapts to the marine environment with temperature 29-30.5 degreeC, salinity 29-31.5 ppt, pH 6.90-7.90 and dissolved oxygen 4.79-8.72 mg/l. Halophila ovalis were found living in high percentage of silt (85.98-96.38%) at both Merambong and Tg. Adang Laut shoals. Halophila ovalis which lived under shade had broader morphs (broader leaf surface and longer petiole) as an adaptation in unstable environment. Thus, the number of shoot density were less than those exposed and so with the biomass too. This plant also had anatomical adaptation due to low light intensity at the marine environment. They had 7-11 lacunae in the rhizome which help in gas transportation.